Application of Reminicence Therapy in Early Prevention Efforts to Reduce the Level of Depression in the Elderly in Harjosari Village, Pekanbaru City: Penerapan Terapi Reminicence dalam Upaya Pencegahan Dini untuk Menurunkan Tingkat Depresi Lansia di Kelurahan Harjosari Kota Pekanbaru - Rusherina, Rusherina; Usraleli, Usraleli; Ira Oktaviani; Alkausyari, Alkausyari (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
The increase in the number of elderly every year requires serious attention and handling because the elderly experience a decline physically, biologically and psychologically which is closely related to economic, social and cultural problems. Social changes that occur in the elderly are cognitive and psychomotor decline. The decline in both functions causes the elderly to experience psychosocial aspects related to the personality of the elderly while psychological changes that occur in the elderly include short-term memory, frustration, loneliness, fear, death, depression, and anxiety. Depression is a mental disorder that shows symptoms: depressed mood, loss of pleasure or interest, feelings of guilt or low self-esteem and reduced self-confidence, eating or sleeping disorders, lack of energy, and decreased concentration. Role changes and decreased social interaction and job loss can leave the elderly vulnerable to mental problems including depression. The increase in the number of elderly every year requires serious attention and handling because the elderly experience a decline physically, biologically and psychologically which is closely related to economic, social and cultural problems. Social changes that occur in the elderly are cognitive and psychomotor decline. The decline in both functions causes the elderly to experience psychosocial aspects related to the personality of the elderly while psychological changes that occur in the elderly include short-term memory, frustration, loneliness, fear, death, depression, and anxiety